2010
DOI: 10.1093/scan/nsq081
|View full text |Cite
|
Sign up to set email alerts
|

‘Willpower’ over the life span: decomposing self-regulation

Abstract: In the 1960s, Mischel and colleagues developed a simple 'marshmallow test' to measure preschoolers' ability to delay gratification. In numerous follow-up studies over 40 years, this 'test' proved to have surprisingly significant predictive validity for consequential social, cognitive and mental health outcomes over the life course. In this article, we review key findings from the longitudinal work and from earlier delay-of-gratification experiments examining the cognitive appraisal and attention control strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
327
4
13

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 450 publications
(367 citation statements)
references
References 46 publications
12
327
4
13
Order By: Relevance
“…Here, we showed that craving could be curbed effectively via a single, clinically relevant strategy that involved cognitively reinterpreting the meaning of an initially craved substance in terms that highlighted its potential longer-term deleterious effects on one's health. In general, such cognitive strategies are known to be effective for regulating emotion in the laboratory and field (26,49), in children and adults (1,26), and for treating psychiatric (50) as well as substance use disorders (18,51).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we showed that craving could be curbed effectively via a single, clinically relevant strategy that involved cognitively reinterpreting the meaning of an initially craved substance in terms that highlighted its potential longer-term deleterious effects on one's health. In general, such cognitive strategies are known to be effective for regulating emotion in the laboratory and field (26,49), in children and adults (1,26), and for treating psychiatric (50) as well as substance use disorders (18,51).…”
Section: Discussionmentioning
confidence: 99%
“…In so doing, this study provides a methodological tool and conceptual foundation for studying this ability across substance using populations and developing more effective treatments for substance use disorders. T he ability to resist immediate gratification by controlling the impulse to consume a desirable-but, in the long run, unhealthy-substance is critical to both mental and physical health (1). This ability is perhaps no more important than for individuals with substance use disorders (SUDs), which are chronic relapsing conditions (2, 3) with staggering social costs (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive control during childhood is a strong predictor of school and social competence 57 , which seems to be a good argument to stimulate bilingualism. However, the reduction in vocabulary and lexical access may have a negative effect on academic performance.…”
Section: R E V I E Wmentioning
confidence: 99%
“…The inhibition of such behaviors that are driven by emotions has been coined "hot" effortful control. Children's performance in such emotionally valenced inhibitory tasks assessing has been shown to predict life-long academic attainment and achievement outcomes, even after controlling for cognitive ability and socioeconomic status [17][18][19].…”
mentioning
confidence: 99%